Casebook in child behavior disorders - Kearney, Christopher A. (Belmont, CA : Wadsworth Cengage Learning, 2013)
This casebook illustrates the rich and arresting nature of disorders that first manifest themselves in childhood while also showing how a child's developmental patterns shape the expression of each disorder. Each complex case demonstrates how each disorder is expressed from presentation through diagnosis and treatment in an effective way. Throughout the book, the author explores the DSM-IV-TR criteria and demonstrates the interaction between developmental and environmental influences for each disorder.
Includes bibliographical references (p. 185-205) and index.
Keywords: Child psychopathology -- Case studies